TEACHING ENGLISH IN MULTILEVEL CLASSES - Sodiqova, Iroda (Educational Research in Universal Sciences, 2023)
The article explores the challenges and strategies associated with “Teaching English in Multilevel Classes”. This instructional context involves students with diverse proficiency levels, requiring educators to adapt their teaching approaches. Key considerations include addressing individual learning needs, employing flexible lesson planning, integrating technology, fostering a collaborative environment, and promoting cultural sensitivity. The abstractemphasizes the importance of continuous assessment, teacher professional development, and creating an inclusive atmosphere for effective language instruction in multilevel classes.